Pengaruh Kesehatan dan Keselamatan Kerja (K3) terhadap Kinerja Pegawai pada Rumah Sakit Umum Daerah Kondosapata’ Kabupaten Mamasa - Isai Limbong Bamba; Milka Pasulu; Jumaidah Jumaidah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
ISAI LIMBONG BAMBA. 2023. The Influence of Occupational Health and Safety on Employee Performance at the Kondosapata Regional General Hospital, Mamasa Regency. Thesis Management Study Program STIM-LPI Makassar (supervised by Dr. Milka Pasulu, S.E., M.Si and Mrs. Jumaidah, S.Sos., M.Sc). The purpose of this study was to examine the effects of the implementation of Occupational Health and Safety (K3) on the performance of employees at Kondosapata' Regional General Hospital, Mamasa Regency. The method used is a quantitative approach, which includes descriptive and inferential aspects. The sample consists of 80 employees, selected by the saturated sample method. The main data was collected through a questionnaire filled out by respondents at the Kondosapata Regional General Hospital. The analysis of the results includes a number of techniques, such as validity testing, reliability testing, hypothesis testing (T test and F test), the coefficients of determination, and the application of linear multiple tests which are carried out by utilizing SPSS version 23.0 software. The results of the analysis reveal that Occupational Health and Safety (K3) factors have a positive and significant impact on the performance of employees in hospitals.